Evaluation of the Selection of the Submersible Pump Specification System of PDAM Tirtauli in Siantar Selatan District, Pematangsiantar City - Yulianti (PT Inovasi Pratama Internasional, 2021)
In this final project, a submersible pump has been applied. From the pump data obtained a capacity of 27.10 l/s. Pump head 14.62 m based on calculations in the field. By using empirical equations it can be determined the main parameters of pump planning, namely specific speed, pressure loss on the pipe wall, length, diameter and type of pipe, number and type of pipe accessories used. By conducting research and measurements in the field, the pipe diameter is 6 inches, the type of Ci and the length of the pipe is 1260 meters using the Hazen William formula and the continuity of flow and pressure loss along the pipe (head losses friction) and pressure losses (head losses minor) is 20.50 meters.